HUBUNGAN TINGKAT PENDIDIKAN DAN PENGETAHUAN IBU TENTANG STATUS GIZI SEIMBANG DENGAN KEJADIAN STUNTING PADA ANAK DI WILAYAH KERJA PUSKESMAS BAAMANG I KABUPATEN KOTAWARINGIN TIMUR - Mika Aprianti; Evy Noorhasanah; Rita Kirana; Muhammad Anwari; Agus Rachmadi (Jurnal Cakrawala Ilmiah, 2024)
Based on the Ministry of Health's Riskesdes in 2018, the stunting prevalence rate in Kotim Regency was 48.84%, the highest in Central Kalimantan. But in 2022 referring to the Indonesian Nutrition Status Survey (SSGI) data from the Indonesian Ministry of Health the stunting prevalence rate in Kotim district was 27.9% and based on the results of the Indonesian Health Survey (SKI) in 2023 the stunting prevalence rate decreased to 18.24% (Central Kalimantan Provincial Health Office, 2023). The type of research used is descriptive analytic with a cross sectional approach, where data collection is done only once to analyze the relationship between the level of education and knowledge of mothers about balanced nutritional status with the incidence of stunting. There is a relationship between knowledge and the incidence of stunting. Stunting is caused by several factors, one of which is maternal factors (maternal knowledge about nutritional status, exclusive breastfeeding and complementary foods (TNP2K, 2017). Lack of maternal understanding about nutrition, exclusive breastfeeding and complementary foods greatly affects the nutritional status of children. Nutrient intake before, during and after childbirth can put children at risk of impaired growth and development, brain structure and function, low productivity, and chronic diseases in adulthood.